REPERTOAR BAHASA MASYARAKAT CINA DI ACEH - Wildan Wildan; Rajab Bahry; Razali Razali (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
This study is about language repertoire of the Chinese community inAceh. The aim of this study is to find out (1) the mastery of variety of languages and (2) the level of language mastery of the Chinese community in Aceh. This study is based on result of research in ten cities in Aceh. The data was collected by usingquestionnaire and interview method. The conclusion of this research are (1) theChinese community in Aceh is included to a group of monolingual, bilingual, andmultilingual community and mastery of many languages, such as Chinese,Indonesian, Acehnese, Bahasa Jamee, Javanese, Sundanese, Bataknese, English,Japanese, Korean, and Arabic; and (2) the level of their mastery toward thelanguages are varied.Their mastery of Indonesian (oral and written) is at the level‘good’. Their mastery toward oral-Chinese is ‘good’, while written-Chinese is‘fair’. Hereinafter, their mastery toward foreign language and vernacular be at thelevel ‘fair’.